The Length-Weight Relationship and Condition Factors of Bullet Tuna Landed at the Tanjung Luar Fishing Port, Indonesia - Evron Asrial; Yasir Arapat; Usma Kurniawan Hadi; Lalu A.T.T.W.S Kalih; Mita Ayu Liliyanti; Erwin Rosadi; Ruly Isfatul Khasanah; Ishani Nelunika Rathnayake (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight • Bullet tuna (Auxis rochei Risso 1810) has been identified (measured, weighed) and analyzed. • The resource status of bullet tuna has been estimated based on body shape and age group. • LWR curve is implemented to describe and express the age group of bullet tuna (immature, adult/mature, old) • This study has resulted the composition and ratio of bullet tuna that is suitable to be caught, fit for consumption and worthy of maturation